THE EFFECT OF CONCEPT ORIENTED READING INSTRUCTION (CORI) ON STUDENTS' READING COMPREHENSION AT EIGHTH GRADE OF SMPN 11 BIMA CITY - Taufik Qurrahman (Graduate Program, University of Islam Malang, 2021)
Abstract Reading is an important point for students to reach potential information, In the process of teaching and learning reading is identical essential. Then, this determines of this research is to determines the extent to which students' reading comprehension skills in reading texts are after being showed by concept-oriented Reading Instruction (CORI).In this study, the study’s objective was to treasure out the significant Effect of concept-oriented Reading Instruction (CORI) on Students’ Reading Comprehension in Narrative Text at the Eighth Grade of Junior High School Negeri 11 Bima city in 2020/2021 Academic Year. Researchers found that the reading comprehension of students at SMPN 11 Bima city is stagnant weak or lacking. There needs to be motivation from the teacher, earlier, researchers are interested in using Cori because it has something to do with motivation in understanding the meaning or reading ability in learning English.The population in this learning were all class VII Junior high school 11 Bima city, the total population was 150 students, the researchers only took two classes, namely class VII-4 as a Quasi- experiment class totaling 20 students, and class VII-7 as a control class group of 20 people, The sample size is 40 students. To study the data, the researcher used the t-test sample formula and statistical calculations.After studying the data, the researcher finished that there was a significant effect on using the Cori strategy in class VIII students of SMPN 11 Bima City, so it can be finished that there is a difference in the average student learning outcomes between learning Cori using and lecture techniques. Constructed on these results, it can be finished that the Zero Hypothesis (Ho) is rejected and, the Alternative Hypothesis (Ha) is accepted. Key Words: CORI Strategy, Reading Comprehension